Action, action, action : the early cinema of Raoul Walsh - Conley, Tom (Albany : State University of New York Press, 2022)
"Studies the force of action, motion, and vision in the early cinema of Hollywood director Raoul Walsh"--
1. On the Lower East Side; Regeneration -- 2. A monkey talks to Sadie Thompson -- 3. Eyes and cockeyes; The cockeyed world -- 4. From Sadie to Mamie; The revolt of Mamie Stover -- 5. Big trees, tall men; The big trail -- 6. Me, my gal, my brother; Me and my gal (1932) -- 7. The good, the bad, The Bowery -- Conclusion. What became of The wrath of the just?
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on June 06, 2022).
JSTOR
Keywords: Walsh, Raoul, -- 1887-1980 -- Criticism and interpretation; Walsh, Raoul, -- 1887-1980; Motion pictures -- History -- 20th century; Motion picture producers and directors -- United States -- Biography; Cinéma -- Histoire -- 20e siècle.; Producteurs et réalisateurs de cinéma -- États-Unis -- Biographies; PERFORMING ARTS / Film & Video / History & Criticism; Motion picture producers and directors; Motion pictures; United States; 1900-1999; Biographies; Criticism, interpretation, etc; History; Biographies; Biographies